Analysis of the relationship between attitudes, training, and perceptions of food handlers on supervision and the implementation of personal hygiene among food handlers - Rahmalia, Vina (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Poor personal hygiene can affect the cleanliness of food provided to patients. A preliminary study conducted at XX Hospital Nutrition Installation found that five food handlers failed to use complete personal protective equipment (PPE), and two food handlers engaged in conversation while preparing food. This research aims to identify factors influencing the implementation of personal hygiene among food handlers at XX Hospital Nutrition Installation. Method: This quantitative study employed a cross-sectional design from November 2019 to March 2020. The sample included 43 food handlers selected through total sampling. Data analysis utilized SPSS and Chi-square tests. Results: The study indicated that 48.8% of food handlers exhibited inadequate personal hygiene, 41.9% had limited knowledge, 53.5% demonstrated negative attitudes, 60.5% did not receive training, and 51.2% perceived inadequate supervision from their superiors. Significant correlations were observed between knowledge (p=0.004), attitude (p=0.000), training (p=0.000), and perception of supervision (p=0.004) with the implementation of personal hygiene. Conclusion: Attitude, training, and perception of supervision significantly influence the adherence to personal hygiene among food handlers at XX Hospital 's Nutrition Installation. It is recommended that the Nutrition Installation enhance supervision of food handlers' personal hygiene and conduct certified training programs on food hygiene and sanitation. Novelty/Originality: This study provides new insights into the relationship between knowledge, attitudes, training, and perceptions of supervision with implementing personal hygiene in the context of hospital food handlers. The findings suggest that although multiple factors influence individual hygiene, a better training and supervision-based approach can significantly improve compliance with hygiene practices, which is an essential contribution to managing food quality in the hospital environment.